1985
DOI: 10.1111/j.1570-7458.1985.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory response of cabbage root fly Delia radicum to the host plant volatile allylisothiocyanate

Abstract: The responses of gravid female cabbage root flies, Delia radicum (L.), to brassica odour and allylisothiocyanate (ANCS) presented in either a discrete plume or uniformly dispersed in air passing through a wind tunnel were investigated. Relatively fast, straight flights occurred in diffuse odour conditions, while in discrete plumes flights were slower with more frequent changes of direction. Flies maintained a constant ground speed and track angle over the straight legs of their flight tracks in two different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
1
30
0
3
Order By: Relevance
“…Only mated gravid females respond to them (Hawkes and Coaker, 1979;Nottingham and Coaker, 1985;Renwick et al, 1992;Roessingh et al, 1992;Simmonds et al, 1994;De Jong and Städler, 1999;Hurter et al, 1999). In a study examining the role of glucosinolates towards oviposition behaviour of the cabbage root fly using egg counts and electrophysiological recordings from tarsal chemoreceptors, Roessingh et al (1992) showed that the D sensilla on segments 3 and 4 of the tarsus of cabbage root fly females contain a sensitive receptor cell for glucosinolates.…”
Section: Cabbage and Turnip Root Flies (Delia Radicum And D Floralis)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only mated gravid females respond to them (Hawkes and Coaker, 1979;Nottingham and Coaker, 1985;Renwick et al, 1992;Roessingh et al, 1992;Simmonds et al, 1994;De Jong and Städler, 1999;Hurter et al, 1999). In a study examining the role of glucosinolates towards oviposition behaviour of the cabbage root fly using egg counts and electrophysiological recordings from tarsal chemoreceptors, Roessingh et al (1992) showed that the D sensilla on segments 3 and 4 of the tarsus of cabbage root fly females contain a sensitive receptor cell for glucosinolates.…”
Section: Cabbage and Turnip Root Flies (Delia Radicum And D Floralis)mentioning
confidence: 99%
“…Gravid females of the cabbage root fly arrive at a hostplant odour source by a series of short upwind flights, landing and reorientating into the wind between flights (Hopkins et al, 1999). The adult female oviposits in the soil close to the stem of Brassica plants (Nottingham and Coaker, 1985;De Jong and Städler, 1999), while damage to the plants is caused by hatched larvae feeding on the roots.…”
Section: The Cabbage Root Fly (Delia Radicum Syn Brassicae) and Thementioning
confidence: 99%
“…Both fly species are stimulated by leaf extracts of cauliflower to lay eggs. Previous studies demonstrate that, after stimulation of anemotaxis by crucifer volatiles, D. radicum detects key compounds on the leaf surface of crucifers through sensilla present on the prothoracic tarsi (Finch & Skinner, 1982; Nottingham & Coaker, 1985; Städler & Schöni, 1990; Roessingh et al , 1992; De Jong et al , 2000). The results of the present study confirm that glucosinolates, either in an extract fraction, or as pure synthetic glucobrassicin at 10 −4 M, stimulate the oviposition behaviour of both fly species.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and chemical stimuli that influence the oviposition behaviour of the cabbage root fly have been extensively investigated by different authors (reviewed in Städler 2002). D. radicum oviposition site selection is influenced by the volatile hydrolysis products of GSLs (Wallbank & Wheatley 1979;Ellis et al 1980;Nottingham & Coaker 1985;Tuttle et al 1988), and plant odour plays an additional role in host selection also after landing . The role of other factors, including non-volatile chemicals on the leaf surface (Roessingh et al 1992b;Hurter et al 1999;De Jong et al 2000) as well as leaf colour (Prokopy & Roitberg 2001) have been investigated.…”
Section: Introductionmentioning
confidence: 99%